FOSO RUMAGES UM BANUA : MODEL REKONSTRUKSI TERHADAP PENDIDIKAN INFORMAL BERBASIS KEARIFAN LOKAL - Lahamendu, Natalia; Kandowangko, Lidya; Andalangi, Jammer; Heydemans, Nency; Tendean, Joshua (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to describe Foso Rumages Um Banua as a reconstructionmodel for informal education rooted in local wisdom. This tradition, alsoknown as the Thanksgiving tradition, is an indigenous practice of theMinahasa people in North Sulawesi, Indonesia. The research was conductedin Minahasa Selatan, an area where this tradition is actively practicedannually. A qualitative research methodology was employed, utilizingobservation, interviews, and document collection techniques to gather datarelated to the Thanksgiving tradition. The collected data was analyzedthrough data reduction, presentation, and verification. The findings revealthat Foso Rumages Um Banua serves as a local wisdom that supports areconstruction model for informal education. Embedded within this traditionare values of communal harmony, cultural representation, andenvironmental protection. These values, expressed through acts ofthanksgiving, embody educational principles that should be passed downthrough generations